Representasi Dewa Surya dalam Bentuk Arca di Jawa - Surya, Pratama Dharma (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
The depiction of the deities in sculptural form was an important aspect of Hindu-Buddha cultural development in the Nusantara from the fifth to the sixteenth centuries. Sculptures of the Surya deity are among the archaeological finds reflecting this cultural influence, especially in Java. This study explores the representation of the Surya deity through a literature review, observations, and descriptive-comparative analysis of seven sculptures found in the administrative regions of East Java, Central Java, and the Special Region of Yogyakarta. This study uses iconographic approach, and the results show that sculptures of Surya deity are characterized by distinctive iconographic features, such as hands in varadahastamudra and/or holding lotus flowers, sitting cross-legged on a lotus pedestal, or standing/sitting on a chariot drawn by seven horses. These representations reflect symbolic concepts associated with fertility, health, and balance in the lives of past societies. This study highlights the iconographic features and symbolic role of Surya deity sculptures as an integral part of Java’s archaeological landscape. === Penggambaran tokoh dewata dalam bentuk arca merupakan bagian penting dari perkembangan kebudayaan Hindu-Buddha di Nusantara pada abad ke-5 hingga ke-16 Masehi. Arca Dewa Surya merupakan salah satu temuan arkeologis yang mencerminkan pengaruh kebudayaan tersebut, terutama di Jawa. Penelitian ini membahas representasi Dewa Surya berdasarkan studi pustaka, observasi, dan analisis deskriptif-komparatif terhadap tujuh arca yang ditemukan di wilayah administratif Jawa Timur, Jawa Tengah, dan Daerah Istimewa Yogyakarta. Penelitian ini menggunakan pendekatan ikonografis dan hasilnya menunjukkan bahwa arca Dewa Surya digambarkan dengan ciri ikonografis khas, seperti tangan bersikap varadahastamudra dan/atau memegang bunga teratai, sikap duduk bersila di atas teratai, atau sikap berdiri/duduk di atas kereta yang ditarik oleh tujuh ekor kuda. Representasi ini mencerminkan konsep simbolis yang terkait dengan kesuburan, kesehatan, dan keseimbangan dalam kehidupan masyarakat masa lalu. Penelitian ini memberikan gambaran tentang ciri ikonografis arca Dewa Surya dan peran simbolisnya di Jawa.